Conclusive evidence of magnetic rotational band in 57Fe: Extending the shears mechanism to the fp shell orbital - S. Basu; G. Mukherjee; S. Rajbanshi; Y. Utsuno; Noritaka Shimizu; S. Nandi; S.S. Nayak; S. Pal; S. Bhattacharyya; S. Chakraborty; Soumik Bhattacharya; Shabir Dar; et al. (Physics Letters B)
A Magnetic Rotational (MR) band in 57Fe nucleus has been newly identified and established from the decreasing behaviour of the experimental electric dipole transition probabilities, B(M1), determined from the measured lifetimes of the states. This becomes the first nucleus in the lighter mass (A<60) region in which, the B(M1) values of an MR band are measured. A single-particle configuration of πf7/2−2⊗ν(p3/2f5/2p1/2)3 has been assigned to this MR band. This configuration, which involves only the negative parity proton and neutron orbitals below and above the Z,N = 28 shell closures, respectively, is a unique one which was not identified before for an MR band. The range of observed angular momenta for this band is congruent with this configuration and the experimental data are found to be in agreement with the SPAC (Shears mechanism with Principal Axis Cranking) and semi-classical calculations. Shell model calculations with GXPF1A interaction reproduce the observed levels in 57Fe including the band head of the MR band. This validates the assigned configurations of this band.